Changing Media Space and Evolution of Digital Culture. - Ahmad, Irfan (Sciences de l'Homme et de la Société; Vol. 14 (2015): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ(Mars), 2015)
This paper tries to provide a brief analysis of the history of changing media space and the evolution of digital culture, with a special focus on the comparative analysis of pros and cons. It highlights the power of new media and that how it helps institutions, government apparatus and the scientific communities, for example, universities in making a participatory environment among citizens and in the dissemination of knowledge and scientific thoughts in a best possible way. In addition, it also provides opportunities to learn with peers without geographical boundaries famously known as: Peer-to-peer learning and helps to develop new skills required in the modern age. But at the same time there are some concerns that need for policy and pedagogical interventions like participatory gap, Transparency and ethical challenges. This is the problem statement of this paper.  الملخص: سيحاول هذا المقال أن يقدم تحليلا وجيزا في مساحة وسائل الإعلام المتغيرة عبر التاريخ وتطور الثقافية الرقمية مع التركيز على الدراسة المقارنة في الجانب الإيجابي والسلبي ويلقي الضوء على قوة وسائل الإعلام الجديدة وعلي أنه كيف يساعد الهيئات والمؤسسات الحكومية والدوائر العلمية مثلا الجامعات في جعل بيئة تشاركية فيما بين السكان في نشر العلوم والمعرفة بصورة أحسن وبأسرع وقت ممكن وفي توفير الفرص للتعلم مع الأقران بلا حدود الجغرافية ما يقال: Peer-to-peer learning وتنمية المهارات الحديثة المطلوبة في عصر الحديث.  ولكن في وقت نفسه هناك بعض الاهتمامات تحتاج التدخلات السياسية والتربوية مثلا تعبية الفجوة التشاركية، الشفافية، والتحديات الخلقية. وهذه هي إشكالية هذا المقال.